PERHITUNGAN JARAK JANGKAU MAKSIMUM PESAWAT UDARA NIR AWAK BPPT UNTUK MISI STRATEGIS DETERMINING = THE MAXIMUM FLIGHT RANGE OF BPPT’S UAV FOR STRATEGIC MISSION - Muliadi, Jemie; Prayitno, Endarmadi A.; Muryanto, Heri T. (Majalah Ilmiah Pengkajian Industri, 2015)
The Agency for The Assessment and The Application of Technology (BPPT, Indonesia) has developed several UAV prototypes for various of mission. The missions to be accomplished were including military purposes and also civilian application. To validate the capability of these UAV in performing their defined mission, there’s a requirement to calculate the flight performance parameters. The relevant parameters were including maximum flight range, maximum altitude, flight endurance, etc. The flight range is a crucial parameter to be determined for a UAV for its suitable mission. Thus, this work will be focused on the Maximum Range determination of PUNA BPPT. The data from BPPT’s UAV flight tests will be processed to obtain the aerodynamic parameters as inputs for maximum flight range calculation. The maximum range resulted were occurred in an optimum value of cruising speed. While varying the cruising speed will affect the maximum range attained, the variation will also be analyzed, and the effect will be concluded. ABSTRAKBadan Pengkajian dan Penerapan Teknologi telah mengembangkan Pesawat Udara Nir Awak untuk berbagai misi. Selain misi yang terkait dengan aplikasi pertahanan dan keamanan, PUNA BPPT dikembangkan pula untuk misi-misi non militer. Sebagai validasi kemampuan PUNA BPPT dalam memenuhi misi terebut, maka perlu diketahui ukuran-ukuran performa yang relevan. Ukuran-ukuran tersebut meliputi,jarak jangkauan terbang maksimun, ketinggian terbang maksimum, ketahanan lama terbang, dan sejenisnya. Jarak jangkauan terbang (range) merupakan parameter yang krusial dalam Operasional Pesawat Udara Nir Awak. Makalah ini menyajikan perhitungan jangkauan terbang maksimum PUNA BPPT. Data hasil uji terbang PUNA BPPT diolah untuk menghasilkan parameter aerodinamika yang akan menjadi masukan dalam perhitungan jarak jangkauan terbang PUNA. Jarak jangkau maksimum ini akan mencapai nilai optimum pada suatu nilai kecepatan jelajah optimum. Maka, variasi kecepatan jelajah akan dianalisa dan efeknya akan disimpulkan terhadap Jangkauan Terbang PUNA BPPT.